The Impact of Live Streaming and Flash Sales on Purchasing Decisions for Pucelle Perfume on the TikTok Shop Platform - Fina Fhariza; Y Yusuf (CV. Media Digital Publikasi Indonesia, 2026)
The development of e-commerce and social media in Indonesia, with TikTok Shop as a leading platform, has transformed consumer behavior to become more responsive to interactive digital promotions such as live streaming and flash sales. However, the decline in Pucelle perfume's popularity index from 9% (2021) to 4-5% (2025), according to Top Brand Award data, indicates marketing strategy issues on TikTok Shop Cirebon, where the brand has not optimally utilized these features compared to competitors like Casablanca and Vitalis. This study analyzes the influence of live streaming (X1: target market, information access, creativity) and flash sales (X2: large discounts, frequency, duration, availability, attractive promotions) on purchase decisions (Y: purchase intent, information processing, conviction, recommendations, repurchase). Employing a quantitative causal-associative method, primary data from an online questionnaire with 130 Pucelle users in Cirebon were analyzed using PLS-SEM via SmartPLS 4.0. The outer model results show validity (loadings >0.70, AVE >0.50) and reliability (Cronbach's Alpha >0.70, CR >0.80). Inner model: R² for purchase decisions = 0.612 (moderate). Hypotheses accepted (H1: path 0.400, t=4.293, p=0.000; H2: path 0.434, t=4.441, p=0.000; H3 simultaneous: F=14.565, p=0.000). Live streaming enhances real-time interaction, while flash sales trigger impulsive urgency. A combination of both is recommended to boost Pucelle's competitiveness in the digital era.